Introduction: Ciphering and Ruling Modern China’s Population - Bréard, Andrea; Christ, Stefan (Journal of the European Association for Chinese Studies, 2025)
The special issue “Ciphering and Ruling Modern China’s Population” focuses on the increasing efforts to quantify the Chinese population beginning in the twentieth century. The introduction explains how it does not understand numbers as neutral entities reflecting objective facts but as cyphers that encode hidden realities and emerge from concrete historical contexts. Furthermore, it summarises the four contributions to the special issue: Drawing on approaches from intellectual and conceptual history as well as the sociology of science, they examine Liang Qichao’s early demand for statistics, attempts to quantify China’s Muslim population, Sun Yat-sen’s evolving obsession with the “400 million Chinese”, and the surprising wealth of statistical production in warlord-ruled Shanxi province. The authors ask why numbers, and statistical ones in particular, became so alluring and even fetishised, despite those involved in the production and use of the numbers being aware of their imprecision. Why did statistics become a sine qua non for governing China’s population? And how did specific numbers become central political terms? The authors also explore how numbers were used to construct arguments about China’s “population”, “society”, and “people” and how these arguments changed over time. 本專刊《近代中國人口的編碼與治理》聚焦二十世紀以來在量化中國人口方面的不懈努力。數字並非中立地反映客觀事實，而是產生於特定歷史背景、用以藏匿現實的密碼。本專刊收錄的四篇論文綜合運用思想史、概念史以及科學社會學的研究方法，分別探討了梁啟超對統計的早期需求、中國穆斯林人口量化的初步嘗試、孫中山對“四萬萬中國人”的執著探究、以及軍閥統治下山西統計工作的驚人成就。並進一步探究了為什麼數位（尤其是統計資料）明明不精確，但時人仍為之癡迷？統計資料何以成為治理中國人口的必要條件？特定數位怎樣成為核心政治術語？統計資料如何被用以建構關於中國"人口"、"社會"及"人民"的論述以及這些論述的歷時性演變。